Prospects for the Use of Cryopreserved Bone Marrow Mesenchymal Stem Cells in the Treatment of Neurological Diseases and Injuries - Kaliuzhka, Vladyslav; Piatykop, Volodymyr; Shchegelska, Olena; Cherniaieva, Oleksandra (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):295